Technologies for water and wastewater treatment - Boari G.; Mancini I.M.; Trulli E. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
The paper first presents a review of the technologies and processes which are used for water and wastewater treatment in order to remove the various constituents of the polluting load: solids, organic carbon, nutrients, inorganic salts and metals, pathogens. A second part describes the advanced processes to reuse treated municipal effluents in agriculture and industries and the main technologies which are used for desalination
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)